Mutation screening of melatonin-related genes in patients with autism spectrum disorders - Thuresson Kent; Landén Mikael; Pedersen Christin; Bremer Anna; Ljunggren Elin; Jonsson Lina; Giacobini MaiBritt; Melke Jonas (BMC, 2010)
Abstract Background One consistent finding in autism spectrum disorders (ASD) is a decreased level of the pineal gland hormone melatonin and it has recently been demonstrated that this decrease to a large extent is due to low activity of the acetylserotonin O-methyltransferase (ASMT), the last enzyme in the melatonin synthesis pathway. Moreover, mutations in the ASMT gene have been identified, including a splice site mutation, that were associated with low ASMT activity and melatonin secretion, suggesting that the low ASMT activity observed in autism is, at least partly, due to variation within the ASMT gene. Methods In the present study, we have investigated all the genes involved in the melatonin pathway by mutation screening of AA-NAT (arylalkylamine N-acetyltransferase), ASMT, MTNR1A, MTNR1B (melatonin receptor 1A and 1B) and GPR50 (G protein-coupled receptor 50), encoding both synthesis enzymes and the three main receptors of melatonin, in 109 patients with autism spectrum disorders (ASD). A cohort of 188 subjects from the general population was used as a comparison group and was genotyped for the variants identified in the patient sample. Results Several rare variants were identified in patients with ASD, including the previously reported splice site mutation in ASMT (IVS5+2T>C). Of the variants affecting protein sequence, only the V124I in the MTNR1B gene was absent in our comparison group. However, mutations were found in upstream regulatory regions in three of the genes investigated, ASMT, MTNR1A, and MTNR1B. Conclusions Our report of another ASD patient carrying the splice site mutation IVS5+2T>C, in ASMT further supports an involvement of this gene in autism. Moreover, our results also suggest that other melatonin related genes might be interesting candidates for further investigation in the search for genes involved in autism spectrum disorders and related neurobehavioral phenotypes. However, further studies of the novel variants identified in this study are warranted to shed light on their potential role in the pathophysiology of these disorders.